Pemberdayaan Masyarakat dalam Pengelolaan Sampah melalui Gerakan Mengubur Sampah - Christian, Yulius Evan (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Indonesia, the world's second-largest waste producer, is experiencing significant impacts on ecosystems and human health due to the discharge of industrial and household waste, including hazardous waste into rivers. Immediate action is needed to prevent further environmental damage. The purpose of this community service is to increase community understanding regarding the importance of processing waste into something useful and of high selling value. This activity was held at the residence of the Chairman of RT.003, Village, Bekasi Regency. The target partners of this activity are 34 villagers. The implementation of socialization uses the method of presenting material using PowerPoint slides and practices on how to make or process organic waste. Before the presentation, the villagers filled out the attendance list, were given a pre-test, and after the presentation of the material, a post-test was conducted to find out the level of understanding of the villagers about the material presented. After data processing is carried out to see whether there is an increase in knowledge or not after filling out the pre-test and post-test, it is obtained that there is a meaningful change or there is an influence from the activities given, namely, after being given socialization, there is a change and the community becomes aware of the socialization material and the activities given, judging from the results of data processing, namely the results of Fcalung > Ftabel were obtained, namely 33.78 > 4.41. So it was concluded that there were meaningful changes before and after the activity. The follow-up to this service is that it needs longer monitoring so that the impact is more visible.